2013
DOI: 10.1039/c3dt32862g
|View full text |Cite
|
Sign up to set email alerts
|

Toward molecular rotors: tetra-N-heterocyclic carbene Ag(i)-halide cubane-type clusters

Abstract: 1,3-Bis(3'-butylimidazol-1'-yl)benzene diiodide (2a), 1,3-bis(3'-but-3''-enyl-imidazolium-3'-yl)benzene diiodide (2b), 1,3-bis(3'-pent-4''-enyl-imidazolium-3'-yl)benzene diiodide (2c), 1,3-bis(4'-butyl-1',2',4'-triazolium-1'-yl)benzene diiodide (2d), or 1,3-bis(4'-butyl-1',2',4'-triazolium-1'-yl)benzene dibromide (2e) was reacted with Ag2O yielding unprecedented tetra-N-heterocyclic carbene-Ag(I)-X cubane-type clusters. These were characterized by (1)H and (13)C NMR spectroscopy, ESI-TOF MS, elemental analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…The AgeC and AgeBr bond lengths fall in the range 2.140(4)e2.161(4) Å and 2.6850(5)e 2.8567(6) Å, respectively. These values are in agreement with those found in other NHC silver halide cubane complexes [71].…”
Section: Synthesis Of the Silver(i) Complexessupporting
confidence: 91%
See 2 more Smart Citations
“…The AgeC and AgeBr bond lengths fall in the range 2.140(4)e2.161(4) Å and 2.6850(5)e 2.8567(6) Å, respectively. These values are in agreement with those found in other NHC silver halide cubane complexes [71].…”
Section: Synthesis Of the Silver(i) Complexessupporting
confidence: 91%
“…During the course of our work, Hollis et al reported the Ag(I)e NHC complex bis((m-1,3-bis(3 0 -butylimidazol-2 0 -ylidene)benzene)-k-C)tetra-m 3 -iodotetrasilver(I) (ImidBu 2 Ag 4 I 4 , 2c), obtained in 67% yield as a white powder by reaction of the pro-ligand ImidBuI (1c) with Ag(I) oxide [71]. Similar to 2b, this complex has a distorted cubane structure with a [Ag 4 I 4 ] core.…”
Section: Synthesis Of the Silver(i) Complexesmentioning
confidence: 97%
See 1 more Smart Citation
“…and O4) and is coordinated to four silver ions ( Figures S3-S5 Comparison of the two structures suggests that the nature of the silver complex formed is strongly influenced by the properties of the counter ion. The soft iodide ion promotes assembly of the neutral Ag 4 I 4 cluster, as observed in the literature with a range of different additional ligands in the fourth coordination position [22][23][24][25]. In contrast, the harder nitrate anion binds only weakly to Ag(I) in complex 2B, acting as an ancillary ligand to the essentially linear N-Ag-N coordination.…”
Section: Accepted Manuscriptsupporting
confidence: 52%
“…The ligand was prepared on the basis of the literature procedures [15]. Li[Fe(bipy)(CN) 4 ]·H 2 O was synthesized according to the modified literature method [16].…”
Section: Methodsmentioning
confidence: 99%